Driving Interaction and Ubiquitous Learning With Mobile Devices: A Pilot Study (Journal on Excellence in College Teaching, 2024)
This pilot study focused on enabling students to proactively use their mobile devices as their own “simultaneous media” tocollaborate with one another, search for topics and ideas on the Internet, and submit findings in real-time in the classroom. Using only their smartphones, students were able to easily access course materials and collaborate in class, at home, or anywhere they had Internet access. By using these tools, students were able to work together in the classroom as apprentice researchers, enabling them to find and analyze ideas and use higher-level cognitive skills to discover, evaluate, generate content, and, moreover, assess their own findings.